Answer:
[tex](f+g)(x)=x^2+2x-5[/tex]
Step-by-step explanation:
Given:
The functions given are:
[tex]f(x)=2x+3\\g(x)=x^2-8[/tex]
To find: [tex](f+g)(x)[/tex]
[tex](f+g)(x)[/tex] is equal to the addition of both the functions. So, we need to add the values of both the functions and then simplify to arrive the final answer.
Therefore, [tex](f+g)(x)[/tex] is given as:
[tex](f+g)(x)=f(x)+g(x)[/tex]
Plug in the values of [tex]f(x)\ and\ g(x)[/tex] and simplify. This gives,
[tex](f+g)(x)=2x+3+x^2-8[/tex]
Combining like terms using commutative property of addition, we get
[tex](f+g)(x)=x^2+2x+3-8\\(f+g)(x)=x^2+2x-5[/tex]
Therefore, the addition of the two functions is simplified to:
[tex](f+g)(x)=x^2+2x-5[/tex]